Exploration of Methanol Utilizing Microbes From Soil and Dung, as Source of Single Cell Protein - Hazra, Fahrizal (Jurnal Ilmu Tanah dan Lingkungan, 2005)
The objectives of this research were to explore methanol utilizing microbes by isolation. selection and collection ofmethanol utilizing microbes from soil and dung. further it will be produced as single cell protein.The experiment covers two steps. i.e. I) Sampling of soil and dungfrom Bogor. Cianjur and Karawang. 2) Laboratoryactivity. consisted of: isolation. selection. identification and collection. The microbes were isolated by using the medium ofTani. et al (/982) and its modification. whereas the methanol utilizing microbes were identified by using standard method ofBergeys Manual of Determinative Bacteriology edition Ijh (/994) and Balow et al. (/99 I). The microbes were then proliferatedby using Medium of Mimura et al. (1978) and its modification. Furthermore the cell were harvested and measured itsnitrogen content. The collection of methanol utilizing microbes was conducted with the standard procedure of soilmicrobiology.This research indicated that from 72 samples of soil and dung were obtained 56 isolates of methanol utilizing microbesthat diverse in number and types. Most of methanol utili:ing microbes were isolated from soil and dung by methanol medium 1% and /.5 % in pH 5 and 7. From 56 isolates were chosen 12 isolates to be identified and made as a data base. and then upt as culture collection at Indonesian Center for Biodiversity and Biotechnology (ICBB). Laboratory of Microbiology and Environmental Biotechnology PPLH. and Laboratory of Soil Biology. IPB. From the 12 isolates. 2 isolates were classified into methylotrophic group and they have big potency to be exploited in producing single cell protein. i.e. MelhylococCJIS capsulatus and Acidomonas methanolica. Between 2 isolates. Methylococcus capsulatus (T2M 1 P 1 Cianjur) have a big potency to be used as a source of single cell protein. due to their high content of protein. i.e. 6.4%. Both of the microbes were not pathogenic for human and animal.